OVERCOMING DISPARITIES IN SCHOOL FINANCIAL MANAGEMENT: THE ROLE OF TECHNOLOGY FOR SCHOOL BURSARS BASIC - Yopi Agusta Fanaturiza; Lailatul Yuliana; Imelda Dian Rahmawati; Hidayatulloh (International Journal of Economic Integration and Regional Competitiveness, 2024)
This study evaluates the challenges and solutions in financial management at SDN Gebang 2 Sidoarjo, focusing on the role of the school treasurer. Data shows that teachers, including the treasurer, generally lack adequate financial administration skills, despite being equipped with technology knowledge that is more focused on teaching. The additional burden of teaching duties and frequent changes in the treasurer position add complexity to financial management. The use of technology such as Microsoft Excel and the government’s ARKAS application has helped alleviate financial administration tasks but still requires additional training. The study concludes that continuous training and adequate organizational support are crucial for enhancing the treasurer’s competency in managing finances effectively and transparently. Recommendations include providing in-depth training, developing specialized training modules, and implementing policies that support stability and reduce the workload of school treasurers